2023
DOI: 10.3389/fonc.2023.1178592
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative, oncologic, and functional outcomes of robot-assisted partial nephrectomy for special types of renal tumors (hilar, endophytic, or cystic): an evidence-based analysis of comparative outcomes

Abstract: PurposeThis study aims to perform a pooled analysis to compare the outcomes of robot-assisted partial nephrectomy (RAPN) between complex tumors (hilar, endophytic, or cystic) and non-complex tumors (nonhilar, exophytic, or solid) and evaluate the effects of renal tumor complexity on outcomes in patients undergoing RAPN.MethodsFour databases were systematically searched, including Science, PubMed, Web of Science, and Cochrane Library, to identify relevant studies published in English up to December 2022. Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…This proximity makes it particularly important to repair these structures with traditional suturing techniques after damage during surgery, which is di cult to achieve with generally less invasive sutureless techniques. Studies have shown that partial nephrectomy for large or endophytic tumors involves longer operative times and a higher risk of surgical complications compared to radical nephrectomy [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…This proximity makes it particularly important to repair these structures with traditional suturing techniques after damage during surgery, which is di cult to achieve with generally less invasive sutureless techniques. Studies have shown that partial nephrectomy for large or endophytic tumors involves longer operative times and a higher risk of surgical complications compared to radical nephrectomy [22][23][24].…”
Section: Discussionmentioning
confidence: 99%